VD_FINDINFO AP / 2009 / 188 vom 6. März 2009 - VD Tribunal cantonal (2009)
INTERDICTION DE L'ARBITRAIRE, APPRÉCIATION DES PREUVES, MOYEN DE DROIT CANTONAL | 328 al. 1 CO, 444 al. 1 ch. 3 CPC, 444 al. 2 CPC